2002
DOI: 10.1021/cm0116830
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Luminescence Properties of Hybrid Materials Containing Europium(III) Complexes Covalently Bonded to a Silica Matrix

Abstract: A new kind of luminescent organic−inorganic hybrid material (denoted Hybrid I) consisting of europium 1,10-phenanthroline complexes covalently attached to a silica-based network was prepared by a sol−gel process. 1,10-Phenanthroline grafted to 3-(triethoxysilyl)propyl isocyanate was used as one of the precursors for the preparation of an organic−inorganic hybrid materials. For comparison purposes, the hybrid material (denoted Hybrid II) in which phenanthroline was not grafted onto the silica backbone of the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(125 citation statements)
references
References 44 publications
6
117
0
2
Order By: Relevance
“…The photoluminescent behaviour of these complexes incorporated in solid matrices is very interesting. The preparation of silica composites containing luminescent complexes seems a promising strategy, since the resulting materials can be prepared at room temperature by employing the sol-gel method, hence avoiding thermal degradation of the complex [4][5][6][7][8]. The SiO 2 matrices also have good mechanical and chemical stability, optical transparency, and are easily prepared using well-known procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescent behaviour of these complexes incorporated in solid matrices is very interesting. The preparation of silica composites containing luminescent complexes seems a promising strategy, since the resulting materials can be prepared at room temperature by employing the sol-gel method, hence avoiding thermal degradation of the complex [4][5][6][7][8]. The SiO 2 matrices also have good mechanical and chemical stability, optical transparency, and are easily prepared using well-known procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Curve 2 in Figure 2 shows the FTIR spectrum of TDI modified silica (SiO 2 -TDI), compared with the spectrum of the unmodified silica, the TDI modified silica exhibited peaks at 2273, 1653, 1605, 1545 and 1472 cm −1 in addition to the peaks of original silica. The peak at 2273 cm −1 can be attributed to the ortho-isocyanate groups of TDI attached to the silica surface, while the bands at 1653 and 1545 cm −1 can be reasonably assigned to the group of -CONH-formed in the reaction [22] , the peaks at 1605 and 1472 cm −1 are reasonably attributed to the phenyl ring of TDI. In addition, the absorbance of surface hydroxyl group became quiet weak.…”
Section: Preparation Of Silica-based Atrp Macroinitiatormentioning
confidence: 91%
“…Curve 2 in Figure 3 shows the FTIR spectrum of TDI modified silica (SiO 2 -TDI), and compared with the spectrum of the unmodified silica, the TDI modified silica exhibited peaks at 2273, 1653, 1605, 1545 and 1472 cm −1 in addition to the peaks of original silica. The peak at 2273 cm −1 can be attributed to the ortho-isocyanate groups of TDI attached to the silica surface, while the bands at 1653 and 1545 cm −1 can be reasonably assigned to the group of -CONH-formed in the reaction [21] , and the peaks at 1605 and 1472 cm −1 are reasonably attributed to the phenyl ring of TDI. The results clearly confirmed that the TDI molecule was covalently linked to silica particles, suggesting successful surface modification of the silica particles with TDI.…”
Section: Preparation Of Silica Macromonomermentioning
confidence: 92%